Controllable Fabrication of Inhomogeneous Microcapsules for Triggered Release by Osmotic Pressure. Issue 42 (25th August 2019) - Zhang, Weixia; Qu, Liangliang; Pei, Hao; Qin, Zhao; Didier, Jonathan; Wu, Zhengwei; Bobe, Frank; Ingber, Donald E.; Weitz, David A.
Abstract: Inhomogeneous microcapsules that can encapsulate various cargo for controlled release triggered by osmotic shock are designed and reported. The microcapsules are fabricated using a microfluidic approach and the inhomogeneity of shell thickness in the microcapsules can be controlled by tuning the flow rate ratio of the middle phase to the inner phase. This study demonstrates the swelling of these inhomogeneous microcapsules begins at the thinnest part of shell and eventually leads to rupture at the weak spot with a low osmotic pressure. Systematic studies indicate the rupture fraction of these microcapsules increases with increasing inhomogeneity, while the rupture osmotic pressure decreases linearly with increasing inhomogeneity. The inhomogeneous microcapsules are demonstrated to be impermeable to small probe molecules, which enables long‐term storage. Thus, these microcapsules can be used for long‐term storage of enzymes, which can be controllably released through osmotic shock without impairing their biological activity. The study provides a new approach to design effective carriers to encapsulate biomolecules and release them on‐demand upon applying osmotic shock. Abstract : Inhomogeneous microcapsules are designed and controllably fabricated to encapsulate biomolecules through a single‐step microfluidic process. The inhomogeneous microcapsules are demonstrated to be preferable for controlled release triggered by osmotic shock. These inhomogeneous microcapsules can be used to encapsulate biomolecules for long‐term incubation and can be triggered by osmotic shock to release the encapsulated biomolecules without impairing their biological activity.